Self-medication in children aged 2 to 5, mediated by their caregivers (Research, Society and Development, 2024)
Self-medication in children is a common practice in Brazil, especially among children aged 2 to 5, whose caregivers resort to medications without medical guidance. This study aimed to identify and analyze the factors leading to self-medication in children within this age group, based on a literature review. Studies published between 2019 and 2024 were included, sourced from databases such as SciELO, PubMed, LILACS, and Google Scholar. The review revealed that many parents self-medicate their children due to difficulty accessing healthcare services, lack of adequate medical guidance, and cultural influences. Most cases involve the use of analgesics and antipyretics to treat symptoms like fever and pain, without considering the risks of improper dosage and adverse reactions. In low-income families, this practice is more prevalent due to the lack of access to private health insurance. The findings indicate that self-medication can lead to severe consequences, such as intoxication, antimicrobial resistance, and delays in diagnosing more serious conditions. It is concluded that educational campaigns and public policies are essential to raise caregivers' awareness of the risks of this practice. Future research should investigate the influence of initial pediatric consultations on parents' self-medication behavior and test customized educational interventions to reduce this practice in different socioeconomic contexts.